EFEKTIFITAS ORGANISASI SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) WATAMPONE - SYAMSURIADI - (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2017)
The Effectiveness of Organization of State Islamic Institute (STAIN)Watampone. This study aims to: understand and uncover the effectiveness of Organization of State Islamic Institute (STAIN) Watampone. This study analyzes the effectiveness of organizations through a variety approaches and competing values include the ability to adapt, sourcing, planning, and productivity and efficiency. As for who becomes the object of research was variable of Effectiveness Organization and analysis using qualitative descriptive. The results of this research showed that the effectiveness of the organization Of State Islamic Institute (STAIN) Watampone based on the dimensions of ability to adapt to changes in the environment shows that is not optimal, and still continue to proceed in response to the demands of the external environment, especially the rules of top-down government, for example, the issue about the demands of quality education, in accordance with the National Standards for Higher education (SNPT), but in the technical implementation is still a lot of fundamental things that need adjustment quickly, especially associated with Tri Dharma College. Similarly in response to the issues that were hot in the community both at the locally, nationally and internationally. It was seen from the low structural design adjustments primarily related to the complexity of the component, and the formalization, but in terms of centralization components had shown good effectiveness with the granting of autonomy to the departements and study program. Furthermore, the effectiveness of the organization in gaining the support resources included in the criteria was not optimal, particularly with regard to the provision of facilities and infrastructure that relies solely on funds from the Revenue Budget and State Revenue Non Tax, Similarly in an increase in the number of lecturers in accordance with the ideal comparison with the number of students. While the organization's ability to got supported from the community in increasing the number of students was very effective as evidenced by the high enthusiasm of prospective students who apply from the year 2012/2013 until 2016/2017. Furthermore, the effectiveness of the organization on the dimensions of planning, shows the level of effectiveness is low, because the vision and mission of the organization was not able to be well understood by all elements of the organization, then the clarity size of the achievement had no time limited and clarity of area coverage is also unclear, and the manufacturing process still need to be involved all stakeholders. Further the effectiveness of Organization in production capability and efficiency, especially in producing qualified scholars still no best ratio between input and output. As well as in scientific publication the national and international level is still very low.Keywords: Efektifitas Organisasi.